2019
DOI: 10.1016/j.cmi.2018.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and the immunological response to infant vaccinations; a double-blind randomized controlled trial

Abstract: The probiotic intervention did not affect the antibody response against S. pneumoniae and B. pertussis toxin in healthy Danish children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Previous studies show no statistical significance between the probiotics group and the placebo group when comparing carriage rate of pneumococcal serotypes and no significant difference in antibody response to PCV13 8,10 . Furthermore, no significant differences between the groups were seen in terms of gender, siblings, breastfeeding, indoor pets, health status since birth, smoking in the household, age or compliance 18 , thus the two groups were compiled for analyses in this study (Table 1).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies show no statistical significance between the probiotics group and the placebo group when comparing carriage rate of pneumococcal serotypes and no significant difference in antibody response to PCV13 8,10 . Furthermore, no significant differences between the groups were seen in terms of gender, siblings, breastfeeding, indoor pets, health status since birth, smoking in the household, age or compliance 18 , thus the two groups were compiled for analyses in this study (Table 1).…”
Section: Resultsmentioning
confidence: 84%
“…It was previously shown that daily administration of a combination of Bifidobacterium animalis ssp. lactis and Lactobacillus rhamnosus GG for a 6-month intervention period did not affect the antibody response against S. pneumoniae in healthy Danish children in terms of geometric mean of the antibody concentrations against 12 S. www.nature.com/scientificreports www.nature.com/scientificreports/ pneumoniae serotypes 8 . In this study, we found that the antibody response to PCV13-vaccination was independent of the pneumococcal carrier status of the children.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A combination of Bifidobacterium animalis ssp. lactis and Lactobacillus rhamnosus GG (LGG) daily was able to decrease IL-6 production in 290 children receiving vaccines for Streptococcus pneumoniae and Bordetella pertussis [66] . Moreover, in mice the administration of immunobiotic Lactobacillus plantarum to the respiratory tracts in acute pneumonia virus infection promoted survival in association with diminished levels of IL-6 [67] .…”
Section: Implications: Gut-liver Axis and Microbiota Modulation As Pomentioning
confidence: 99%
“…Invasion of microorganisms and absorbed metabolites affects circulating lymphocytes and the intestinal microbiota is disrupted, leading to a change in the immune response group (Fig. 4) (Sørensen et al 2019). In particular, interleukin IL-6 is one of the substances that are significantly elevated in patients with SARS-CoV-2 disease, especially in the nonsurvival group.…”
Section: Microbiome As a Barrier To Virus Infectionmentioning
confidence: 99%